MENANAMKAN NILAI KARAKTER KEJUJURAN MELALUI PERMAINAN TRADISIONAL CONGKLAK PADA ANAK USIA 5-6 TAHUN - Yuliantika (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2023)
The background of this research is the low value of the character of honesty in children aged 5-6 years at Kasih Ibu Kindergarten, Tenayan Raya District, Pekanbaru City. For this reason, it is necessary to carry out an action through the traditional congklak game. This type of research is Classroom Action Research (CAR). The subjects taken were children aged 5-6 years in class B2 consisting of 12 students. Data collection techniques in this study were through observation and documentation sheets. The data analysis technique used to obtain data through Cycle I which consisted of 2 meetings and Cycle II which consisted of 2 meetings was using the percentage formula = f/n x 100%. The results of the study instilling the character value of honesty through the traditional congklak game increased, this can be seen from the initial data so that cycle II meets 2. Initial data (32%), cycle I (54%) and cycle II (95%). So that the increase in instilling the character value of honesty through the traditional game of congklak obtained an average percentage of 60%. The implication of this study is that teachers must instill the character value of honesty starting from an early age.